A Physicist View of COVID-19 Airborne Infection through Convective Airflow in Indoor Spaces - Luis Alfredo Anchordoqui; Eugene M. Chudnovsky (Ital Publication, 2020)
General Idea: Naturally produced droplets from humans (such as those produced by breathing, talking, sneezing, and coughing) include several types of cells (e.g., epithelial cells and cells of the immune system), physiological electrolytes contained in mucous and saliva (e.g. Na+, K+, Cl-), as well as, potentially, several infectious agents (e.g. bacteria, fungi, and viruses). In response to the novel coronavirus SARS-CoV-2 epidemic, which has become a major public health issue worldwide, we provide a concise overview of airborne germ transmission as seen from a physics perspective. We also study whether coronavirus aerosols can travel far from the immediate neighbourhood and get airborne with the convective currents developed within confined spaces. Methodology: Methods of fluid dynamics are utilized to analyse the behavior of various-size airborne droplets containing the virus. Study Findings: We show that existing vortices in the air can make a location far away from the source of the virus be more dangerous than a nearby (e.g., 6 feet away) location. Practical Implications: Our study reveals that it seems reasonable to adopt additional infection-control measures to the recommended 6 feet social distancing. We provide a recommendation that could help to slow down the spread of the virus.